2020
DOI: 10.3389/feart.2020.00339
|View full text |Cite
|
Sign up to set email alerts
|

Pore Network Modeling of Core Forming Melts in Planetesimals

Abstract: Early in the history of the solar system, planetesimals were differentiated into metallic cores. In some planetesimals, this differentiation took place by percolation of the denser core forming liquid through a lighter solid silicate matrix. A key factor in core formation by percolation is the establishment of a connection threshold of the melt. In this work, we report new results from pore network modeling of 3D microtomographic images of 11 synthetic olivine aggregates containing Fe-FeS melt. Our results dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Furthermore, a possible primary metal melt loss below the metal fraction found in Seymchan aggregates is hindered by the low mobility of high dihedral angle melts as the system approaches textural equilibrium. Energetic considerations (Walte et al, 2007) and experimental studies (Bagdassarov et al, 2009;N eri et al, 2020;Solferino et al, 2020) showed a connectivity threshold in the range of 10-15 vol%, incidentally the highest primary metal fraction found so far in olivine aggregates (Seymchan- Walte et al, 2020). It is difficult to pinpoint when this equilibrium and pinch-off is achieved during annealing, but a twofold grain-size increase should be sufficient, which was reached during an early stage considering a grain-size increase over one to two orders of magnitude while transforming chondritic to pallasite textures.…”
Section: Grain Growth In the Dunitic Mantle And The Cause Of Grain-si...mentioning
confidence: 99%
“…Furthermore, a possible primary metal melt loss below the metal fraction found in Seymchan aggregates is hindered by the low mobility of high dihedral angle melts as the system approaches textural equilibrium. Energetic considerations (Walte et al, 2007) and experimental studies (Bagdassarov et al, 2009;N eri et al, 2020;Solferino et al, 2020) showed a connectivity threshold in the range of 10-15 vol%, incidentally the highest primary metal fraction found so far in olivine aggregates (Seymchan- Walte et al, 2020). It is difficult to pinpoint when this equilibrium and pinch-off is achieved during annealing, but a twofold grain-size increase should be sufficient, which was reached during an early stage considering a grain-size increase over one to two orders of magnitude while transforming chondritic to pallasite textures.…”
Section: Grain Growth In the Dunitic Mantle And The Cause Of Grain-si...mentioning
confidence: 99%
“…To segregate, it should form a connected network along the silicate grain boundaries. Due to the high surface tension between the solid silicates and the liquid metal, this only occurs at a metal content of 20 vol% (Bagdassarov et al, 2009;Néri et al, 2020;Solferino et al, 2020), well above the 10 vol% present in chondrites. Thus, magma oceans inside planetesimals are a mixture of liquid silicate (∼ 45 vol%), olivine crystals (∼ 45 vol%) and liquid metal droplets (∼ 10 vol%).…”
Section: Did Global Magma Oceans Exist On Small Bodies?mentioning
confidence: 99%
“…Yoshino et al 2003;Terasaki et al 2005;Roberts et al 2007;Walte et al 2007;Bagdassarov et al 2009a;Ghanbarzadeh et al 2017). Solferino et al (2020) argued that sluggish kinetics in olivine-metallic liquid systems explain much of this discrepancy, with long run duration experiments implying critical melt thresholds of around 14 vol%, consistent with the results of numerical simulations which suggest values of 10-17 vol% (Ghanbarzadeh et al 2017). Experimentally determined interfacial energies support the assertion that segregation is more feasible for S-rich melts used in most experimental studies, and that dihedral angles and critical thresholds are considerably higher for low S metallic melts (Neri et al 2019).…”
Section: Experimental Studies Of Percolation Of Core-forming Meltsmentioning
confidence: 99%
“…Percolation is an inherently slower process and only a viable mechanism for planetesimal differentiation if it is able to account for core segregation within, at most, a few Myr. For a fully interconnected melt network based on models of Ghanbarzadeh et al (2017) and using a simple Darcy flow type calculation, Solferino et al (2020) estimated core segregation in a 100 km radius body in < 1 Myr. By contrast, highpressure centrifuge experiments by Bagdassarov et al (2009b) imply that segregation of Fe-S liquid is an order of magnitude too slow to account for core-formation in planetesimals.…”
Section: Experimental Studies Of Percolation Of Core-forming Meltsmentioning
confidence: 99%